15h-42=-6h-39

Simple and best practice solution for 15h-42=-6h-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15h-42=-6h-39 equation:


Simplifying
15h + -42 = -6h + -39

Reorder the terms:
-42 + 15h = -6h + -39

Reorder the terms:
-42 + 15h = -39 + -6h

Solving
-42 + 15h = -39 + -6h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '6h' to each side of the equation.
-42 + 15h + 6h = -39 + -6h + 6h

Combine like terms: 15h + 6h = 21h
-42 + 21h = -39 + -6h + 6h

Combine like terms: -6h + 6h = 0
-42 + 21h = -39 + 0
-42 + 21h = -39

Add '42' to each side of the equation.
-42 + 42 + 21h = -39 + 42

Combine like terms: -42 + 42 = 0
0 + 21h = -39 + 42
21h = -39 + 42

Combine like terms: -39 + 42 = 3
21h = 3

Divide each side by '21'.
h = 0.1428571429

Simplifying
h = 0.1428571429

See similar equations:

| log(4)*(5x+3)=1 | | r=9cm | | -6x+7=5x+40 | | m^2+m-35=0 | | 7t^2-22t+7=0 | | (x+20)+3x=90 | | 2x+4(x-3)=12 | | 12=-7+v | | -56-6x-5x=43 | | -16t^2-11t+120=0 | | -16t^2-11t+120=h | | 14+23= | | 0=8-3(6-6x) | | .5y+(2x+5)=180 | | f(3)=12+3x | | s+8=-13.5 | | 4x-6x-7=7 | | 2x+9+7x-4=4x+7 | | 11x-154=-5x+54 | | 3(2y-3)=5(y+4) | | 30+8+7+10+25-4+9+25-3+6-5=108 | | x^2+2x-15=15 | | H+9.7=-9 | | x^3-2x^2-41x-56=0 | | 3xy+2x=4y | | 3(x+5)=6x+15 | | 4x+7=2x+9+7x-4 | | 4.1=d-5.1 | | 3.1x-1.6=5 | | 3=2x+1(x) | | (x)(x)+4x=117 | | 6(a+2b)+8b-16b= |

Equations solver categories